Challenges faced by the Southern African Development Community (SADC) in conflict transformation: the case of the Lesotho Conflict from 1994-2017 - Moyo, Elson (Midlands State University, 2018)
The post-Cold War period has been characterised by increased intra-state conflicts in most African states which have overstretched the United Nations’ (UN) capacity to respond to all conflicts that occur in various regions across the globe. This has resulted in an observable relative decrease in the involvement of the UN in African internal conflicts and a subsequent increase in African regional organisations being involved in various conflict handling mechanisms within their respective communities as provided for in Chapter VIII of the UN Charter. Among the mechanisms being adopted is conflict transformation which is a relative new phenomenon. Just like other sub-regional organisations in Africa, the SADC has had challenges in conflict transformation as vindicated by recurrent internal conflicts in the DRC, Lesotho and Mozambique. The study therefore sought to examine challenges being encountered by the SADC in its efforts to facilitate conflict transformation in the region using the Lesotho conflict from 1994 to 2017 with a view to generalise findings to the whole region. The selection of the theory is premised on conflict transformation supported by the human needs theory. The study adopted a qualitative approach to collect and analyse data. In-depth interviews which were conducted in Zimbabwe and Lesotho complemented data collected through desk search.